2020
DOI: 10.21203/rs.3.rs-104711/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mathematical Analysis of a model for Chlamydia and Gonorrhea Codynamics with Optimal Control

Abstract: A model for Chlamydia trachomatis (CT) and Gonorrhea codynamics, with optimal control analysis is studied and analyzed to assess the impact of targetted treatment for each of the diseases on their co-infections in a population. The model exhibits the dynamical feature of backward bifurcation when the associated reproduction number is less than unity. The global asymptotic stability of the disease-free equilibrium of the co-infection model is also proven not to exist, when the associated reproduction number is … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In the absence of tools to change sexual networks, a vaccine will be necessary to stop infection transmission. Chlamydia trachomatis and gonorrhea co-dynamics models with optimum control analysis have been studied and examined to assess the impact of targeted treatment for each of the diseases on their co-infections in a population [11]. Mathematical modeling and study of the transmission dynamics of blinding trachoma with the impact of awareness programs and found a lack of competent health care systems and public awareness programs to blame for the outbreak of the blinding trachoma disease [12].…”
Section: Literature Surveymentioning
confidence: 99%
“…In the absence of tools to change sexual networks, a vaccine will be necessary to stop infection transmission. Chlamydia trachomatis and gonorrhea co-dynamics models with optimum control analysis have been studied and examined to assess the impact of targeted treatment for each of the diseases on their co-infections in a population [11]. Mathematical modeling and study of the transmission dynamics of blinding trachoma with the impact of awareness programs and found a lack of competent health care systems and public awareness programs to blame for the outbreak of the blinding trachoma disease [12].…”
Section: Literature Surveymentioning
confidence: 99%
“…Recent trends in epidemiological research revealed that applying non-integer order differential equations is vital in obtaining good results for dynamical systems. The classical mathematical models of the integer-order derivatives have been greatly employed in studying infectious diseases [10] , [11] , [12] , [13] , [16] , [17] , [18] , [19] , [47] , [27] , [28] , [23] , [24] , [25] . For instance, Omame et al [9] considered and analyzed an integer-order model for the dynamics of Human papillomavirus and Chlamydia trachomatis using optimal control.…”
Section: Introductionmentioning
confidence: 99%